Defect-induced resonances in photonic microdisk resonators for enhancement of nanoparticle – resonance mode interaction. Issue 1627 (7th January 2014) - Ostrowski, M.; Duan, X.; Yi, Y.
ABSTRACT: We present results of theoretical and experimental studies of whispering-gallery modes in optical microdisk resonators interacting with subwavelength dielectric particles. We predict theoretically and confirm by direct observations that, contrary to the generally accepted models, both peaks of the particle-induced doublet of resonances are red shifted with respect to the position of the initial resonance.